Left fower vena cava - Armand Ugon, César; Soto, José; Kamaid, Emil; Belloso, Rogelio (Cirugía del Uruguay, 1977)
A case of left lower vena cava was found during the course of lumbar sympathectomy. Embryologic and clinico-pathologic aspects of this rare anomaly are discussed by the authors.